USM, NCIA TO COLLABORATE IN SCIENCE@ALOR SETAR PROJECT - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
ALOR SETAR, 8 August 2016 – The Kedah Mentri Besar, Datuk Seri Ahmad Bashah Md. Hanipah welcomes the collaboration between Universiti Sains Malaysia (USM) and the Northern Corridor Implementation Authority (NCIA) in advancing education and economic development in the state of Kedah.